Impelementasi AI Chatbot Sebagai Support Assistant Website Universitas Nurul Jadid Menggunakan Algoritma BiLSTM - Rianto, M. Erfan; Furqon, Ainul (Kalam Nusantara Institute, 2024)
This research aims to implement an AI-based chatbot as a virtual assistant to support information services at Nurul Jadid University. The chatbot is designed using the Bidirectional Long Short-Term Memory (BiLSTM) algorithm, a deep learning model capable of understanding and responding to conversations naturally. With this chatbot, it is expected to improve the efficiency and effectiveness in providing information to the public, as well as being the first step for Nurul Jadid University in utilizing AI technology to improve service quality. Furthermore, this research will also analyze the extent to which AI-based chatbots can help reduce the workload of administrative staff in answering questions frequently asked by the public and prospective students. The chatbot is expected to be the first line of defense in answering basic questions, allowing administrative staff to focus on more complex tasks. The results of this research are expected to be a reference for other universities in implementing AI-based chatbots to improve information and communication services with the community.